Skin Temperature, Stratum Corneum Water Content and Transepidermal Water Loss Distributions During Running (Journal of Fiber Bioengineering and Informatics, 2018)
This study examined the trends in skin temperature, Stratum Corneum Water Content (SCWC),Transepidermal Water Loss (TEWL) and subjective sensations during running exercises. Ten healthymale subjects performed exercises wearing cotton briefs in a climate chamber controlled at an airtemperature of 27 ∼ 28 °C and a relative humidity of 50%. Following a rest for 20 mins on a chair (Rest),subjects exercised on a motorised treadmill at 4 km/h walking speed for 20 mins (walk) followed by a7.2 km/h (medium run) and 12 km/h (high run) running speed for 10 min, respectively. The SCWC andTEWL were measured at pre-exercise, end-walk, end-medium run and end-high run. Skin temperatureswere obtained by infrared thermograms for every 5 mins. The main findings were summarized as follows:Skin temperature in chest, abdomen, under arm, upper arm, forearm, hand, ventral thigh and ventralleg were significantly lower during walk, medium & high run than at rest by 0.13 ∼ 0.73, 0.36 ∼ 1.78,0.35 ∼ 2.24 °C, respectively. Skin temperature in dorsal thigh, popliteal fossa was lower within 1? orhigher by 0.11 ∼ 1.28 °C in dorsal leg and foot during exercises than at rest. In accordance with theregions of declines of skin temperatures, SCWC and TEWL doubled and elevated four times. Exerciseswere rated significantly higher for perception of humidity, heat and overall discomfort than rest. Wediscussed how dynamic exercises induce significantly different skin temperature, SCWC and TEWL onhuman body, which have profound influence on subjective perception of thermal factors, humidity anddiscomfort. The results of this study suggested that fall in skin surface temperature during dynamicexercising were related to thermal factors, such as evaporation due to skin sweat.